Security, privacy and trust in modern data management (Springer, 2007)
This book provides a comprehensive guide to data management technologies with respect to security, privacy and trust. After the introductory part that offers a perspective on privacy and security issues in the modern digital world, the contributions from leading researchers are grouped into sections on data and system security, privacy-enhancing techniques, digital asset protection, and selected topics on privacy and security in ambient intelligence. Overall, the book delivers, from information on the ethical and legislative background, to chapters on the state-of-the-art technologies such as access control, identity management and digital rights management to advice on implementing fair information practices and preventing security and privacy violations